Comparison Between Two Different Design Concepts of 4- Implant Assisted Mandibular Complete Overdenture:- periimplant bone height changes (International Journal of Scientific Research and Management (IJSRM), 2021)
Abstract: Purpose: This study was accomplished to evaluate the bone height changes radiographically and the reliability of use either two posterior short or inclined implants with two conventional anterior implants retaining mandibular overdenture. Materials and methods: Ten male mandibular completely edentulous patients were divided in two equal groups after delivered complete dentures. For the first group (short implant design- group A) two vertical implants were inserted in the canine areas and two short vertical implants were inserted in the 1st molar area. For the second group (inclined implant design- group B) two vertical implants were inserted in the canine areas and two 30o distally inclined implants were inserted in the second premolar area. Digital standardized periapical radiographic assessment for horizontal and vertical alveolar bone height changes was carried out at T0 (immediately), T6 (6 months), T12 (12 months) and after mandibular complete overdenture insertion. Result: 1. VBL decrease significantly with advance of time in both groups during the time intervals. The highest VBL around the implants was noted in the 1st six months followed by the 2nd six months, the highest amount of total VBL observed with the interval T0-T12, followed by the interval (T0-T6) and the inclined implant group showed significant higher total VBL than short implant group at the intervals T0-T6 and T0-12. 2- HBL decreased significantly with advance of time in both groups. For short and inclined implant group, the highest amount of total HBL observed with the interval T0-T12, followed by the interval (T0-T6). Short implant group showed significant higher total HBL than inclined group at the interval T0-T6 and T0-T12. Conclusion: Within the limitations of this clinical radiographic study it can be concluded that (1) The 30o distally inclined implants inserted in the posterior areas for assisting mandibular complete overdenture induce vertical bone loss more than the axially inserted implants (short or conventional implants). (2) The short implants inserted in the posterior areas for assisting mandibular complete overdenture induce horizontal bone loss more than the axially inserted implants. Keywords: Short implants, O-ring ball attachment, VBL, HBL.